2016
DOI: 10.1152/japplphysiol.00692.2016
|View full text |Cite
|
Sign up to set email alerts
|

Bouncing on Mars and the Moon—the role of gravity on neuromuscular control: correlation of muscle activity and rate of force development

Abstract: On our astronomical neighbors Mars and the Moon, bouncing movements are the preferred locomotor techniques. During bouncing, the stretch-shortening cycle describes the muscular activation pattern. This study aimed to identify gravity-dependent changes in kinematic and neuromuscular characteristics in the stretch-shortening cycle. Hence, neuromuscular control of limb muscles as well as correlations between the muscles' pre-activation, reflex components, and force output were assessed in lunar, Martian, and Eart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 50 publications
4
27
0
Order By: Relevance
“…However, when information about the drop height is uncertain or unknown, neuromuscular activity and muscle shortening are reduced dramatically prior to GC in the unknown vs known vs cheat condition by approximately 10% (Tables and ). This is in accordance with prior studies that found reduced pre‐activation in conditions where subjects were faced with unpredictability in jumping or landing tasks and impact loads induced by altered gravity . Thus, it seems to be a general phenomenon that when the motor system is not able to adequately predict the loading, pre‐activation is reduced .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…However, when information about the drop height is uncertain or unknown, neuromuscular activity and muscle shortening are reduced dramatically prior to GC in the unknown vs known vs cheat condition by approximately 10% (Tables and ). This is in accordance with prior studies that found reduced pre‐activation in conditions where subjects were faced with unpredictability in jumping or landing tasks and impact loads induced by altered gravity . Thus, it seems to be a general phenomenon that when the motor system is not able to adequately predict the loading, pre‐activation is reduced .…”
Section: Discussionsupporting
confidence: 91%
“…Two aspects might be important in interpreting these findings. The first aspect deals with proactive modulations prior to the event of GC, and the second aspect with the compensatory reactions after touch‐down . The next sections will discuss both aspects in detail.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the most recent studies about musculoskeletal changes due to partial gravity exposure is the study of Ritzmann et al ( 2016 ) which is not included in this systematic review because it was not published during the time of the present literature search. The authors measured biomechanical parameters of a bouncing movement (often referred to as skipping) during a partial gravity parabolic flight (Mars and Moon parabolas).…”
Section: Discussionmentioning
confidence: 99%